Evaluasi Kinerja Minggu I Perkuliahan Program Pasca Sarjana Universitas Negeri Makassar - Herman Herman; Sapto Haryoko (Seminar Nasional LP2M UNM, 2019)
This study aims to determine the performance of the first and second week of lectures in the Postgraduate Program in the even semester 2018-2019. The approach used is a quantitative approach using descriptive analysis. The population used is all study program students within the scope of the UNM post graduate program, both master and doctoral study programs. The sampling technique in this study is the Non Probability Sampling technique, which is a sampling technique that does not provide equal opportunity or opportunity for each element or population member to be selected as a sample. The data collection technique used was a questionnaire / instrument Performance Week I Lectures that have been developed by the Center for Quality Assurance Makassar State University with average data analysis techniques. The results showed that the performance of the first and second week of the UNM post graduate program showed an average value of 10 assessment indicators was 3.67 in the Good category. While the performance of the first and second weeks of lectures in the Public Administration Study Program with an average rating of 10 assessment indicators was 2.91 in the Fair category, the Social Sciences Education Study Program with an average value of 3.59 in the Good category. Geography Education study program with an average value of 4.00 in the Very Good category, Educational Technology Study Program with an average value of 3.77 with a Very Good category.